2002
DOI: 10.1046/j.1440-1681.2002.03673.x
|View full text |Cite
|
Sign up to set email alerts
|

Decrease In Catechol‐O‐Methyltransferase Activity In The Liver Of Streptozotocin‐Induced Diabetic Rats

Abstract: 1. The present study compared the activity of catechol- O-methyltransferase (COMT) in the liver and plasma of streptozotocin (STZ)-induced diabetic rats with that in normal rats. The activity of COMT was estimated by the metabolism of noradrenaline to metanephrine (MN), both measured by high-performance liquid chromatography with electrochemical detection. 2. Formation of MN was decreased in the liver of STZ- diabetic rats compared with normal rats. The amount of MN was also decreased in plasma obtained from S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…This activation of the adrenoceptor β1, as demonstrated in this study, is combined with the well-known increase of noradrenaline content [38] and catecholamine metabolism [45]. This effect is likely to be due to a decrease in catechol-O-methyltransferase activity in a rat model of type 1 diabetes when stressed [48]. We were able to confirm these results in our rat model of type 1 diabetes.…”
Section: Discussionsupporting
confidence: 86%
“…This activation of the adrenoceptor β1, as demonstrated in this study, is combined with the well-known increase of noradrenaline content [38] and catecholamine metabolism [45]. This effect is likely to be due to a decrease in catechol-O-methyltransferase activity in a rat model of type 1 diabetes when stressed [48]. We were able to confirm these results in our rat model of type 1 diabetes.…”
Section: Discussionsupporting
confidence: 86%
“…Hepatic and kidney functions, as well as the enzymes involved in phase I and phase II metabolism, underwent apparent changes in animals under diabetic status (Nadai et al, 1990;Sato et al, 1991;Watkins and Sherman, 1992;Runge-Morris and Vento, 1995;Raza et al, 1996;Engels et al, 1999;Tuñon et al, 1991;Wang et al, 2002;Borbás et al, 2006;Sindhu et al, 2006). Thus, it is not surprising that the metabolic behavior of mangiferin after its oral administration was subjected to great changes in rats under diabetic status compared with that in conventional rats.…”
Section: Discussionmentioning
confidence: 99%
“…The expression levels of several hepatic and intestinal cytochrome P450 (P450) isozymes, such as CYP1A1, -1A2, -1B1, -2B1, -3A1, -3A2, -3A4, -4A1, -4A2, and -2E1 (Raza et al, 1996;Engels et al, 1999;Borbás et al, 2006;Sindhu et al, 2006), as well as sulfotransferases (SULTs), UDP-glucuronosyltransferases (UGTs), and catechol-O-methyltransferase (COMT) (Runge-Morris and Vento, 1995;Tuñon et al, 1991;Wang et al, 2002) involved in phase II metabolism are altered in STZ-induced diabetic rats. Furthermore, an increase in the hepatic blood flow rate (Sato et al, 1991), a higher incidence of hepatic impairment (Watkins and Sherman, 1992), and kidney function impairment (Nadai et al, 1990) were also reported in diabetic rats.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, experimentally induced hyperglycemia has been reported to produce a significant increase in the catecholamine levels in different areas of the brain (Ramakrishnan et al, 2003). In addition, hypoinsulinemia and hyperglycemia have been shown to alter COMT, BDH and TH activities, which could explain the monoaminergic dysregulation observed (Gupta et al, 1992;Muñoz et al, 1984;Wang et al, 2002). Thus, amitraz's a 2 -adrenergic receptors action could contribute either directly or indirectly, through insulin dysregulation, to the observed effects on monoaminergic neurotransmitters.…”
Section: Discussionmentioning
confidence: 99%